Abstract 279: Angiography Utilization in LVO Drip‐and‐Ship Patients: Comparing Air and Ground - Rahul Rao (Stroke: Vascular and Interventional Neurology)
Introduction Patients with acute intracranial large vessel occlusions (LVO) in the drip‐and‐ship model are transferred from an outside hospital (OSH) to a comprehensive stroke center (CSC) after receiving thrombolysis. In our practice, while most of these patients go directly to the angiography suite (DTA), some of them spontaneously recanalize and may not need mechanical thrombectomy (MT). We aim to assess the impact of transport modality on the efficacy of tPA‐induced recanalization by assessing rates of groin puncture, MT, and clinical outcomes. Methods We retrospectively evaluated 270 patients from 2020‐mid 2022 with either confirmed or suspected LVO in our healthcare network who received tPA at an OSH and were transported by either air or ground transport to our spoke hospital (CSC) with the intention of receiving MT. We compared baseline characteristics and then applied linear regression with propensity score matching to compare the air and ground groups. Between the two groups, we looked at the difference in the rates of change in NIHSS between OSH and TTH (delta NIHSS), groin puncture rates, rate of receiving mechanical thrombectomy (MT), rate of angiography alone without MT, and modified Rankin Scale (mRS) at 90 days. Results Of the 270 patients evaluated, 1 patient was excluded due to missing transport modality. 130 (48.33%) were transferred by ground transport and 139 (51.67%) by air. Baseline characteristics were similar between the air and ground groups with the exception of OSH NIHSS which was higher in the air group (13.59±8.3 vs. 10.4±7.81, p<0.001). In a linear regression model, air transport was not a significant predictor of improvement of NIHSS from OSH to CSC (p=0.69, R2=0.002) or groin puncture rate (OR=1.5, 95% CI 0.412‐ 5.471, p=0.54). Of the 198 confirmed LVO on CTA, 47.26% of air patients received MT compared with 48.74% (OR: 1.1, p=0.62) of ground patients. 11.32% of these confirmed LVO patients who were transported by air received angiography without mechanical thrombectomy compared to 11.68% of ground patients (OR: 2.1, p=0.1). A linear regression model with propensity matching did not show transport modality as a predictor of mRS at 90 days (p=0.32, R2=0.14). Conclusion LVO patients who receive tPA and are transferred by air directly to the angiography suite have a higher baseline NIHSS than those transported by ground. Mode of transport does not seem to predict changes in NIHSS or 90 day mRS in this population. Groin puncture, mechanical thrombectomy, and angiography without MT rates are similar between these groups. Mode of transport alone may not influence angiography utilization or clinical outcome so distance between sites and speed of transport should be used to determine whether air or ground is the better choice in each individual case.